(untitled) (Bangladesh Rice Journal, 2021)
Strengthening the early warning system to forecast extreme weather and provide action-oriented advisories may increase rice yield as well as enhance the income of the farmers through minimizing risks and losses, if proper use of the generated advisory is ensured. This study assessed the importance and impact of weather forecast based advisory service (WFBAS) in Bangladesh. Literature review and field experimental data were used in a sensitivity analysis to show the impact of WFBAS on rice production. Available literatures suggested that the weather based advisory service would enhance rice yield by around 6.7-10%, but the experimental findings revealed that yield advantage could be 21.48%. Besides, the adoption of this technology would reduce the cost of cultivation by 12%, whereas the aggregate impact would increase the farmers’ profit by 25%. In the sensitivity study, we considered the production and price of Aman and Boro seasons (actual and government procured prices for 2018-19) and assumed only 6.70% yield increase with 5% farmers adopting of WFBAS. As such, additional 0.172 million tons will be added to the national rough rice production and thus the nation will be benefited by 3143 million Bangladeshi taka (BDT) at the actual farmgate price and it would be 4478 million BDT at the government procured price. The return on one BDT investment in this technology would be 51-73 BDT based on actual and procured prices. The projection showed enhenced production of the rough rice at 0.119 million tons and 0.214 million tons by 2025 and 2030, on which the additional return would be BDT 2441 and BDT 5223 million at the projected actual farmgate price and BDT 3522 and BDT 6979 million at the projected Government procured price, respectively. Hence, the successful implementation of the WFBAS will help to develop resilient rice farming communities, minimize livelihood risk, reduce the cost of production, utilize resources efficienty, and enable the farmers to take maximum benefit from favorable weather conditions through improved agricultural extension services. Finally, the enhanced yield and loss reduction will help to achieve the target of Sustainable Development Goal (SDG) by 2030 through sustaining rice production in Bangladesh under changing climate. Bangladesh Rice J. 25 (1) : 51-74, 2021